2020
DOI: 10.1090/conm/746/15004
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances on the non-coherent band surgery model for site-specific recombination

Abstract: Site-specific recombination is an enzymatic process where two sites of precise sequence and orientation along a circle come together, are cleaved, and the ends are recombined. Sitespecific recombination on a knotted substrate produces another knot or a two-component link depending on the relative orientation of the sites prior to recombination. Mathematically, sitespecific recombination is modeled as coherent (knot to link) or non-coherent (knot to knot) banding. We here survey recent developments in the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…The first knot that was shown to be algebraically slice but not slice by Casson and Gordon [2] was the two-bridge knot B (25,2). Since the appearance of a prime of even power in the first homology introduces challenges, we consider a related family of examples, the set of four two-bridge knots {B (25,1), B (25,24) In general, if there is a smoothing that converts a knot K into a knot J, then K # −J bounds a Mobius band in the four-ball. The bounds based on Theorem 7 continue to apply.…”
Section: Smoothing Distancementioning
confidence: 99%
See 1 more Smart Citation
“…The first knot that was shown to be algebraically slice but not slice by Casson and Gordon [2] was the two-bridge knot B (25,2). Since the appearance of a prime of even power in the first homology introduces challenges, we consider a related family of examples, the set of four two-bridge knots {B (25,1), B (25,24) In general, if there is a smoothing that converts a knot K into a knot J, then K # −J bounds a Mobius band in the four-ball. The bounds based on Theorem 7 continue to apply.…”
Section: Smoothing Distancementioning
confidence: 99%
“…In the reverse direction, Moore and Vazquez [23] showed that T (2, 5) is unique among positive torus knots T (2, m), with m square-free, for which such a move exists. The paper [24] reports on extensive computer searches that have discovered chiral smoothings for the knots 8 8 and 8 20 . If K supports a chiral smoothing, then we will see in Theorem 1 that a single band move converts K # K into K # −K, where −K denotes the mirror image of K with string orientation reversed.…”
Section: Introductionmentioning
confidence: 99%
“…In the first example, we take time to discuss what it shows in regard to a question about band surgeries on knots posed in [12]. We refer the reader to that paper and [19, Section 3] for standard definitions surrounding band surgery. Example Consider the two‐strand 1‐twist on the unknot K shown in Figure 5.…”
Section: Two‐strand Twists Of Odd Ordermentioning
confidence: 99%
“…Band surgery is of interest in low-dimensional topology, in particular in knot theory, and in the study of surfaces in fourmanifolds. It is of independent interest in DNA topology; for a more detailed commentary on this perspective, we refer the reader to [18,Section 5;26], which review the relevance of band surgery to the study of DNA.…”
Section: Introductionmentioning
confidence: 99%